2019
DOI: 10.17159/2078-516x/2019/v31i1a6058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of low-level laser therapy and exercise for knee osteoarthritis

Abstract: Background: Knee Osteoarthritis (KOA) is a prevalent, chronic disorder with excessive functional, social and economic burdens. The goal of treatment is to alleviate the symptoms and slow the progression. Documenting the effects of exercise and LLLT as co-modalities in the management of KOA allows practitioners to implement this management tool as part of KOA rehabilitation, resulting in the earlier discharge from a supervised rehabilitation setting.  Objective: The purpose of this study was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Mechanistically, LLL therapy can reduce the severity of pain by lowering prostaglandin E2, inhibiting the onset of pain, and activating substances that control the inflammatory process [29]. Our results are also consistent with those of a study that examined the effectiveness of LLL therapy and exercise in the treatment of knee osteoarthritis using the WOMAC index to assess pain and functionality, showing good improvement on 24 questions in the WOMAC index stated [30]. Furthermore, our results agree with those of a meta-analysis and systematic review on the safety and effectiveness of LLL therapy in OA knee patients, which concluded that LLL therapy demonstrated significant differences in WOMAC score [31].…”
Section: Discussionsupporting
confidence: 88%
“…Mechanistically, LLL therapy can reduce the severity of pain by lowering prostaglandin E2, inhibiting the onset of pain, and activating substances that control the inflammatory process [29]. Our results are also consistent with those of a study that examined the effectiveness of LLL therapy and exercise in the treatment of knee osteoarthritis using the WOMAC index to assess pain and functionality, showing good improvement on 24 questions in the WOMAC index stated [30]. Furthermore, our results agree with those of a meta-analysis and systematic review on the safety and effectiveness of LLL therapy in OA knee patients, which concluded that LLL therapy demonstrated significant differences in WOMAC score [31].…”
Section: Discussionsupporting
confidence: 88%
“…All studies, except one, which was a quasi-randomised trial [ 25 ], were RCTs and all trials employed a parallel group design. Nineteen studies compared the adjunctive EPT plus exercise therapy to a placebo EPT and exercise [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], whilst 22 compared against exercise only [ 9 , 11 , 19 , 20 , 22 , [34] , [35] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [57] ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen trials compared two groups [ 11 , 23 , 25 , [28] , [29] , [30] , 33 , 36 , 39 , 41 , [43] , [44] , [45] , 48 , 49 , 54 ], 15 included three groups [ 9 , 19 , 20 , 22 , 27 , 31 , 34 , 37 , 38 , 40 , 46 , 47 , 51 , 55 , 56 ], five compared four groups [ 21 , 24 , 42 , 50 , 52 ], one compared five groups [ 57 ] and one trial had six different arms, comparing three EPTs to placebo counterparts [ 26 ]. The number of groups eligible for inclusion is shown in Table 1 , with two groups included in 27 studies [ 11 , 19 , 20 , [23] , [24] , [25] , 28 , 30 , 33 , 36 , 39 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , 53 , 54 , 57 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,6] Thus therapeutic exercise and symptom relief treatment modalities offered by biokineticists and physiotherapists are important for optimal OA management, [3] particularly as evidence shows a favourable effect compared with sedentary individuals. [7][8][9] The above research highlights the indispensable role each profession plays in the management of OA at the different phases of the rehabilitation process.…”
mentioning
confidence: 99%